An analysis of treaties for the exchange of information for tax purposes impacting a South African retail sector taxpayer and financial institutions trading in the Southern African development community region - Van Schalkwyk, Johannes Murray (Department of Finance and Tax, 2015)
Based on recent international tax developments, global revenue authorities have identified a need for the exchange of taxpayer information (EOI) to identify both tax evasion and tax avoidance. This will impact the South African Development Community (SADC) tax payers and financial institutions by increasing the need for additional administrative capacity to identify and report such information, and for revenue authorities to share such information in appropriate circumstances. A number of bilateral and multilateral treaties are currently applicable to SADC taxpayers that regulate the exchange of information by revenue authorities. An analytical comparison between these treaties was performed to identify deviations from the Model Tax Convention (MTC) of the Organisation for Economic Cooperation and Development (OECD). Treaties included in the analysis are those relevant for the South African retail sector trading in various African countries. The comparison of the recent SADC peer reviews of exchange of information revealed significant deficiencies in certain treaties and domestic laws regarding the identification of beneficial owners, bank secrecy, confidentiality rules and underlying document retention, and insufficient EOI agreements are in place. Significant work in amending domestic legislation and administrative capacity building is therefore still required for countries in the SADC region before they can be admitted as parties to the OECD Multilateral Convention on Mutual Administrative Assistance in Tax Matters. Additional investment in IT systems for revenue authorities will be crucial to handle and keep up with this increased information demand. Information will need to be collected, retained and reported using the agreed XML data standards. Conversely, financial institutions and taxpayers will also need to adjust their own tax systems in order to identify reportable information, and be prepared to comply with ad hoc or periodic requests from revenue authorities, even if it involves the tax affairs and information of third parties. EOI increases the risk for the infringements of a South African retail taxpayer's rights to privacy, confidentiality, just administrative action, access to information and access to courts.